GENDER AND ECONOMIC EMPOWERMENT IN THE DIGITAL AGE (CAHIERS MAGELLANES-NS, 2024)
This research paper examines how gender interacts with economic empowerment within the context of an ever-changing digital environment. Technology is dismantling divisions between nations and peoples around the world – but how does this transformation affect men and women’s economic opportunities and results? This research “mixed methods” in the sense that it includes the use of large data sets for quantitative analyses as well as interviews and case studies for qualitative assessments. The results demonstrate that although digital technologies have created limitless platforms for women to pursue economic prospects, barriers still exist in terms of ability to access the digital space, skills, and sociocultural practices. In the end, the paper addresses policy issues and measures which may be taken in order to harness the power of ICT for the benefit of equality in economics.